Handbook of methods in cultural anthropology - Bernard, H. Russell (Harvey Russell), 1940-; Gravlee, Clarence C. (Rowman & Littlefield, 2015)
The Handbook of Methods in Cultural Anthropology, now in its second edition, maintains a strong benchmark for understanding the scope of contemporary anthropological field methods. Avoiding divisive debates over science and humanism, the contributors draw upon both traditions to explore fieldwork in practice. The second edition also reflects major developments of the past decade, including: the rising prominence of mixed methods, the emergence of new technologies, and evolving views on ethnographic writing. Spanning the chain of research, from designing a project through methods of data collection and interpretive analysis, the Handbook features new chapters on ethnography of online communities, social survey research, and network and geospatial analysis. Considered discussion of ethics, epistemology, and the presentation of research results to diverse audiences round out the volume.